Technical aptitudes of senior adolescents - Beresnevičienė, D. (Psichologija, 1993)
The present paper reveals the investigation data of VIII and IX forms pupils in Lithuanian general education schools, using the Differential Aptitude Tests (DAT). 1100 pupils have been studied to determine the factors influencing the level of understanding mechanical reasoning and space relations. The experimental investigation has shown the direct correlation between the above types of aptitudes. The high parameters of technical aptitudes of pupils depend on their inclination for technical activities, engineering interests, age and sex.
Keywords: technical aptitudes; age; gender